How do atomic code uncertainties affect abundance measurements in the intracluster medium?. Issue 2 (17th March 2020) - Mernier, François; Werner, Norbert; Lakhchaura, Kiran; de Plaa, Jelle; Gu, Liyi; Kaastra, Jelle S.; Mao, Junjie; Simionescu, Aurora; Urdampilleta, Igone
Abstract: Accurate chemical abundance measurements of X‐ray‐emitting atmospheres pervading massive galaxies, galaxy groups, and clusters provide essential information on the star formation and chemical enrichment histories of these large‐scale structures. Although the collisionally ionized nature of the intracluster medium (ICM) makes these abundance measurements relatively easy, the underlying spectral models can rely on different atomic codes, which brings additional uncertainties on the inferred abundances. Here we provide a simple, yet comprehensive comparison between the codes SPEXACT v3.0.5 (cie model) and AtomDB v3.0.9 (vapec model) in the case of moderate, charged‐coupled device‐like resolution spectroscopy. We show that in cool plasmas ( kT  ≲ 2 keV), systematic differences up to ∼20% for the Fe abundance and ∼45% for the O/Fe, Mg/Fe, Si/Fe, and S/Fe ratios may still occur. Importantly, these discrepancies are also found to be instrument‐dependent, at least for the absolute Fe abundance. Future improvements in these two codes will be necessary to better address questions on ICM enrichment.